Comparison Of Acupressure Therapy With Message Effleurage To Reduce The Pain Intensity Of Dysmenorrhea In Adolescent Women At SMP Negeri 2 Air Joman Village, Asahan District Year 2021 - Lolita Nugraeny (Sean Institute, 2023)
Based on the initial survey that the researchers conducted on May 18, 2021 at SMPN 2, out of 10 students who experienced menstrual pain, 7 students (70%) and 3 students (30%) did not experience menstrual pain. Therefore, the researcher decided to conduct research in class. This is because primary dysmenorrhea usually occurs during adolescence, which is about 2-3 years after the first menstruation. Researchers conducted interviews with 7 female students who experienced dysmenorrhea, that 2 said mild pain, 3 moderate pain, 2 severe pain and there were still many female students who did not know about acupressure and effleuage massage as a pain reliever during menstruation that is safe, cheap, without cost. Respondents only treated menstrual pain using eucalyptus oil, rested in bed, and some did nothing. To find out the comparison of Acupressure therapy with Message Effleurage on reducing the intensity of dysmenorrhea pain in young women at SMP Negeri 2 Air Joman Village, Asahan Regency in 2021.The type of research used in this research is Quasi-Experimental (Pseudo-Experimental) with a two-group comparison pretest-posttest design.Desain penelitian ini yaitu pretest dan posttest control group design.The population in this study were all young women who experienced dysmenorrhea in class X totaling 20 people with the provision that 10 people were in the acupressure therapy group and 10 people in the massage effleurage group.The dysmenorrhea pain intensity scale before acupressure therapy was carried out was M = 5.60. SD = 1.603, minimum value = 3 and maximum value = 10. And after acupressure therapy is done, M = 0.90. SD = 0.788, minimum value = 0 and maximum value = 2. The dysmenorrhea pain intensity scale before effleurage massage is performed is M = 5.40. SD = 1.603, minimum value = 3 and maximum value = 8 and after massage effleurage is M = 0.90. SD = 0.671, minimum value = 0 and maximum value = 2. The t value for acupressure therapy is 16.672 and the p value = 0.000 while the t value for massage effleurage is 14.261 and the p value = 0.000. The calculated t value of each intervention > t table = 1.761, as well as the p value <α = 0.05, acupressure therapy is more effective in reducing dysmenorrhea pain intensity than effleurage massage..